Delay along the care-seeking journey of patients with ocular surface squamous neoplasia in Kenya - Stephen Gichuhi; Joy Kabiru; Alain M'bongo Zindamoyen; Hillary Rono; Ernest Ollando; Joseph Wachira; Rhoda Munene; Timothy Onyuma; Mandeep S. Sagoo; David Macleod; Helen A. Weiss; Matthew J. Burton (BMC, 2017)
Abstract Background In Africa, accessing eye health services is a major challenge. Ocular surface squamous neoplasia (OSSN) is a substantial ocular health problem in Africa related to solar UV light exposure and HIV infection among other risk factors. The disease causes visual loss and even death in advanced cases. This study was conducted to assess referral pathway and treatment delay for patients with OSSN in Kenya. Methods Adults with conjunctival lesions presenting to four eye centres were asked about their occupations, when they noticed the growth, health facilities visited in seeking care, cost of consultation, surgery, medicines and histopathology and dates at each step. The time-to-presentation was divided into quartiles and correlates analysed using ordinal logistic regression. Results We evaluated 158 first-time presenters with OSSN. Most were women (102 [65%]), living with HIV (78/110 tested [71%]), with low to medium income (127 [80%]). Most of the HIV patients (49/78 [63%]) were in antiretroviral care programs. About half (88/158, [56%]) presented directly to the study centres while the rest were referred. Indirect presenters sought care earlier than direct presenters (median 2.0 months vs 5.5 months) and travelled a shorter distance to the first health facility (median 20 km vs 30 km) but had surgery later (median 12.5 months vs 5.5 months). Visits beyond the first health facility for indirect presenters markedly increased delay (median 7.3, 29.0, 37.9, and 32.0 months for 1-4 facilities, respectively). Delay was associated with number of health facilities visited (adjusted ordered OR = 9.12; 95%CI 2.83-29.4, p < 0.001) and being female (adjusted ordered OR = 2.42; 95%CI 1.32-4.44, p = 0.004). At the time of presentation at the study centres for surgery the median tumour diameter in both directly and indirectly presenting patients was 6 mm (p = 0.52) and the histological spectrum of OSSN was similar between the groups (p = 0.87). Conclusions Referral delays definitive treatment for OSSN. Women were more likely to experience delay. Despite regular contact with the health system for those with known HIV infection, delays occurred. Early detection and referral of OSSN in the HIV service might reduce delays, but reassuringly delay did not give rise to a larger proportion with more advanced grade of OSSN.